Investigating the Capability Approach: How Long-Term Unemployed People in Finland Perceive Their Access to Commodities, Conversion Factors and Capabilities - Ahonen, Tiina; Mäki-Opas, Tomi; Kouvo, Antti; Toikko, Timo (Springer Science and Business Media LLC, 2025)
Capability Approach (CA) extends our understanding of wellbeing by underlining the importance of freedoms. There is a need to operationalize CA components for empirical measurement in different settings and population groups. This study investigated the conversion process from perceived resources to perceived capabilities by investigating the role of perceived conversion factors (personal and contextual) among a particular population group of Finnish long-term unemployed persons (N = 511, year 2016), aged 20–64 years, not receiving activation services, recruited through a service system and registers (random sampling). We used the label “perceived” to highlight that our approach was subjective, meaning that we measured respondents’ own perceptions of their commodities, conversion factors and capabilities. Data were collected in the PROMEQ project using a structured, self-employed questionnaire. Perceived capabilities were measured on a 7 + 1 item scale of self-reported capabilities. The main statistical methods applied were crosstabs with chi² tests, Confirmatory Factor Analysis (CFA) and Structural Equation Modelling (SEM). Long-term unemployed perceived poorer capabilities compared to the general Finnish population. Long-term unemployed men perceived poorer capabilities compared to long-term unemployed women. CFA indicated the data fit with the CA. The SEM model supported the theoretical assumptions of CA: perceived commodities associated with perceived capabilities strongly but indirectly through perceived social and environmental conversion factors. Group analysis (SEM) demonstrated, that between genders the CA-models were slightly differentiated. The results indicate the need for more effective capability promotion, and for targeted practices acknowledging variety of circumstances of the long-term unemployed. CA could offer a comprehensive tool for this task.